Effects of 20 minutes neuro-priming with and without pre-task motivational music on swimming performance among male state swimmers - Xang, Soon Ye (2020)
Neuro priming is a process of using the transcranial direct current stimulation (tDCS) to increase plasticity in the brain prior to an activity. Pre-task motivational music serves as an ergogenic effects prior to an activity that consists of rhythm, tempo, harmony, and melody This study investigated the effect of using 20 minutes of neuro-priming with or without pre-task motivational music on the swimming performance, skill-related performance, anxiety and self-efficacy level among the male state swimmers. Fourteen healthy male swimmers (age: 15.50 ± 1.4) were randomly assigned into three research conditions, Group 1 sham condition (control), Group 2 neuro-priming without music, and Group 3 neuro-priming with motivational music. This study is a cross-over study design with all participants completed all three research conditions separated by one-week of resting period in-between intervention. After the one week of resting, participants needed to go through the same procedure with different research conditions. Anthropometry and physiological profile of all participants were measured. First session involved power test (standing long jump and vertical jump), anaerobic (50m) and aerobic (400m) performance with Group 1 or Group 2 or Group 3 in random order. Before the anaerobic and aerobic swimming performance, participants were required to complete the CSAI-2R and self-efficacy level questionnaires. Participants require to wear Halo Sport neuro-priming headset for 20 minutes with or without motivational music, and during the sham condition (without any stimulation). Motivational music were selected based on BMRI-3. Data were analysed by the Repeated Measure ANOVA. There were significant changes in the anaerobic swimming performance (50m). However, cognitive anxiety, somatic anxiety and self-confidence showed no significance changes in three research conditions. Anaerobic swimming performance (50m) can be improved by using neuro-priming with motivational music without any additional physical training.